2021
DOI: 10.1101/2021.05.18.444545
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In pursuit of a better broiler: A comparison of the inactivity, behavior, and enrichment use of fast- and slower-growing broiler chickens

Abstract: Selection for rapid growth has produced heavier, more efficient broiler chickens, but has also introduced health and welfare issues, which may cause or be caused by inactivity. Rapid growth may also limit the performance of motivated behaviors, whereas the provision of enrichment may increase these behaviors and general activity. This study aimed to evaluate the inactivity, behavior, and enrichment use of 2 fast- (CONV) and 12 slower-growing broiler strains [categorized as fastest (FAST), moderate (MOD) and sl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
0
4
0
1
Order By: Relevance
“…The frequency for exploratory and foraging behaviour might be influenced by genetics and husbandry systems (Yan et al., 2021), part of the animal's personality (Garnham and Løvlie, 2018) and range use (Ferreira et al., 2021). In addition, environmental enrichment including litter substrate (Monckton et al., 2020a) and other objects, higher space allowance (Bach et al., 2019) and (elevated) structures (Dawson et al., 2021) will promote exploration and foraging behaviour (Riber et al., 2018). Active exploratory and foraging behaviour in turn supports the locomotor and health status of the broilers.…”
Section: Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The frequency for exploratory and foraging behaviour might be influenced by genetics and husbandry systems (Yan et al., 2021), part of the animal's personality (Garnham and Løvlie, 2018) and range use (Ferreira et al., 2021). In addition, environmental enrichment including litter substrate (Monckton et al., 2020a) and other objects, higher space allowance (Bach et al., 2019) and (elevated) structures (Dawson et al., 2021) will promote exploration and foraging behaviour (Riber et al., 2018). Active exploratory and foraging behaviour in turn supports the locomotor and health status of the broilers.…”
Section: Assessmentmentioning
confidence: 99%
“…The connection between locomotion and the hybrid of the animals is undisputed. Generally, slower growing broiler hybrids (hybrids with a growth rate of less than 50 g/day (Dixon, 2020; Dawson et al., 2021)) are less susceptible to develop locomotor problems as compared to fast growing hybrids (Dixon, 2020; Rayner et al., 2020). The mobility of broilers has a large impact on welfare.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the factors not directly related to the enrichment are genetics, stocking density, and light intensity. Genetics play a major role in the activity level exhibited by broilers, where for example, fast growth rates may hamper the use of enrichments, but variation may also exist within genotypes of similar growth potential ( Almeida et al, 2012 ; Dawson et al, 2021 ). De Jong et al (2021) showed that although the fast-growing genotype used the enrichment less than the slower-growing genotype, the positive impact on overall activity level was similar for both genotypes.…”
Section: Stimulating and Modifying Broiler Behavior By Provision Of B...mentioning
confidence: 99%
“…Birim metrekare alanda barındırma yoğunluğu hayvan refahı ile ilgili en önemli konulardan birisi olup (13,23), aynı barındırma yoğunluğu ölçüsünün deneysel ve ticari koşullardaki etkisi yavaş ve hızlı gelişen piliçlerde farklı olabilmektedir (24). Yavaş gelişen etlik piliçlerde normal ve korku davranışlarının hızlı gelişenlere göre farklı olduğu bilinmektedir (5,6,25). Ancak deneysel koşullarda yapılan çalışmalar genelde etrafı sınırlı daha dar alanlarda yapılmaktadır ve bu hayvanların yürüme, koşma gibi uzun bir alanda hareket edebileceği davranışları sınırlandırmaktadır.…”
Section: Bulgularunclassified